Examining the structure of the fashion industry in Ghana in ensuring the successful adoption of sustainable approach - Akosua Mawuse Amankwah; Edward Appiah; Charles Frimpong; Anthony Kent (Center for Science and Technology, IAIN Surakarta, 2023)
The structure of the fashion industry in various geographical regions, along with its production history and practices, plays a pivotal role in shaping the adoption and implementation of sustainable strategies. This study examines the fashion industry’s structure in Ghana as a fundamental step in considering the adoption and implementation of sustainable strategies. To facilitate the selection of respondents for this preliminary study, we employed a Google survey, utilizing a snowball technique to identify participations in the two major cities in Ghana. The survey specifically targeted fashion producers operating within the small and medium-sized enterprises (SMEs) with retail outlets. Collected data from Google Forms were collated with Microsoft Excel and subsequently analyzed. The findings unveiled that young businesses often operate as sole proprietorship, with their founders serving as lead designers, primarily selling directly to end users. While previous studies have documented similar findings, this study connects these observations to the adoption of sustainable strategies in businesses where where owners, who also serve as creative heads, make significant decisions that can influence the practice of sustainable strategies. Furthermore, the study highlights that sustainability and sustainable practices are relatively new to SMEs in Ghana. It recommends further research to gauge the awareness and willingness to adopt circular strategies, given the industry towards industrialization.